Drug interactions between voriconazole, darunavir/ritonavir and tenofovir/emtricitabine in an HIV-infected patient treated for Aspergillus candidus lung abscess. (August 2015) - Becker, A; Sifaoui, F; Gagneux, M; Desprez, S; Vignoli, P; Huguet, D; Froidure, M; Leduc, D; Legout, L
We report an unusual case of pulmonary aspergillosis in a patient with AIDS and we demonstrated the drug-drug interactions between voriconazole, darunavir/ritonavir and tenofovir/emtricitabine. The combination darunavir-ritonavir-voriconazole should be avoided.